Genome Sequence of Novoherbaspirillum sp. UKPF54, a Plant Growth-Promoting Rhizobacterial Strain with N(2)O-Mitigating Abilities, Isolated from Paddy Soil - Gao, Nan (Microbiol Resour Announc, 2020)
Novoherbaspirillum sp. strain UKPF54, a plant growth-promoting rhizobacterium with the ability to mitigate nitrous oxide emission from agriculture soils, has been successfully isolated from paddy soil in Kumamoto, Japan. Here, we report the whole-genome sequence of this strain.